Adapting instruments and modifying statements: the confirmation method for the inventory and model for information sharing behavior using social media - Yahaya, Tiny Azleen; Idris, Khairuddin; Suandi, Turiman; Ismail, Ismi Arif (Growing Science, 2018)
This study aims to confirm the information sharing behavior using social media scale and to vali-date every item and make it reliable as an inventory by using Exploratory Factor Analysis (EFA). The researcher adapted the measuring instruments for every latent construct from the literature and customized the items to suit this particular study. The study sent the revised questionnaire to 262 respondents in order to gather the pilot study data and able to get 163 filled ones as final data. The set of questionnaires consists of 66 items that assess the 6 constructs. Data is analyzed using SPSS AMOS Version 21.0. The results show that every construct achieved its Bartletts’ Test of Spherici-ty 6.0 with the re-sult of Information Sharing Behavior .000 and .871; Intention .000 and .782; Belief Expectancy .000 and .911; Attitude Influence .000 and .925; Readiness For Change .000 and .959; and Self-Efficacy .000 and .902. The entire item of the construct has exceeded the minimum limit of 0.7 reli-ability of Alpha Cronbach value to achieve the Internal Reliability. The new integrate model has been proposed due to this finding.